Predictive Value of NT-PRO-BNP for Morbidity and Mortality among Patients of COPD without Underlying Left Ventricular Dysfunction - Hina Khan, Aasia Mazhar Shah, Rabia Qayoom Shaikh, Naila Masood Siddiqui, Imran Ali Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Elevated pro BNP level is associated with increased morbidity and mortality in various cardiac and pulmonary conditions, also considered a valuable prognostic tool in acute exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) without underlying left ventricular dysfunction and also for prognosis of the disease. Objective: To assess the predictive value of proBNP for morbidity and mortality among patients with AECOPD patients without underlying left ventricular dysfunction and on follow up. Study Design: Prospective Cohort Setting: All Medical Wards & Pulmonology Ward– Liaquat University Hospital Hyderabad. Duration of Study: Six months, May 2022 –December 2022 Subjects and methods: 217 diagnosed patients of COPD (132 male & 85 female) were enrolled by non-probability consecutive technique. All these patients were followed by measuring estimated NT-pro-BNP levels. The patient was followed up at day 0, 3rd day indoor, and post discharge for 6th month .Patients were excluded from any form of LV dysfunction or other pulmonary diseases. Results: The mean age was 52.02 ±3.72 years. There were 39.2% females and 60.8% males. COPD stage I was observed in 16 (7.4%), stage II in 81 (37.3%), stage III in 52 (24%), and stage IV in 68 (31.3%) patients. The mean PaO2 was found to be 87.96 ±8.55%. In-hospital morbidity was observed in 77 (35.5%) whereas in-hospital mortality was observed in 54 (24.9%) patients. A significant mean difference of in NT-pro-BNP level was observed in between groups. The mean Pro BNP was significantly higher on 0 day , reduced on 3rd day but after 6month its value again raised, i.e., 142.27 ±11.63,127.56 ±13.67 and 145.68±16.89 respectively (p-value <0.001). Conclusion: A significantly higher NT-pro BNP was associated with mortality and morbidity despite of normal LV function in indoor patients of COPD. Persistence elevated Pro BNP has been demonstrated positive predicted values. Keywords: NT-pro-BNP, acute exacerbation of Chronic Obstructive Pulmonary Disease, left ventricular dysfunction.